Mechanic protection gloves used in waste sorting industry: suitable as passive method to sample for fungal burden - Viegas, Carla (2021)
Background: The high prevalence of airborne bacterial and fungal species in forklift cabinets from waste sorting units has already been described. Aspergillus spp. species are filamentous fungi commonly found in different environmental compartments, where they thrive as saprophytes. Several sections are reported as being mycotoxins producers. In Portuguese waste industries, personal protective equipment, such as mechanical protection gloves (MPG) are of mandatory use. During their use, sweat is released, and consequently, the material humidity and temperature inside the glove increase leading to favorable conditions for the microorganism’s growth. This study intends to assess the fungal and mycotoxins contamination present in MPG as a potential passive sampling method to assess occupational exposure.